Relation of Number of Living Children and Long-Acting and Permanent Contraceptive Methods in West Nusa Tenggara Province (ICMM 2015) - Ruth Rejeki Sianturi, S; Damayanti, R; Siagian, F P (KnE Life Sciences, 2019)
Long Acting and Permanent Contraceptive Methods (LAPMs) is a highly effective contraceptive method for fertility control. The use of LAPMs in NTB is still low compared to non- LAPMs use. This study aimed to determine the correlation between the number of live children and the use of LAPMs after controlled by age, education, occupation, decision making and information exposure from health workers in NTB. This cross sectional study was conducted to all married woman aged 15-49 years, with the samples of the woman of childbearing age who use contraception, using data of Monitoring and Evaluation on Contraceptive Use in East Java and NTB Province 2015 conducted by Center for Health Research Universitas Indonesia. Data were collected through interview guidelines, and multivariate analysis was performed by binomial log regression test. The results showed that the proportion of > 2 live children was 24.9%, and the proportion of the number of live children ≤ two children was 15.2% and had a significant relationship to the use of LAPMs (p = 0.005 OR = 1.63 CI 95% = 1.118 - 1.80). Recommendations for the woman of childbearing age in NTB who have children > 2 were counseled on the use of LAPMs, and for the woman of childbearing age who had live children, ≤ two children were given health promotion related to the LAPMs preference to set the number of children. Keywords: Contraception, Log Term Contraceptive Method, Number of live Children